Technological Development of an Instant Product Based on Fermented Purple Corn (Zea mays L.) Beverage - José Meléndez; Oscar Malpartida; Nancy Ascención Chasquibol (Biology and Life Sciences Forum)
Chicha de güiñapo (ChG) is an ancestral beverage from the culture and gastronomy of Arequipa, Peru. This traditional drink is made from purple corn (Zea mays L.), cultivated across various Peruvian regions. Purple corn is renowned for its nutritional content and high bioactive compound value, such as antioxidants (20.5 ± 2.0 μmol TE/g), total phenolic compounds (2.5 ± 0.3 mg GAE/g), and anthocyanins (1.8 ± 0.2 mg/g). This research aimed to explore the technological development of an instant powder product derived from chicha de güiñapo (ChG) utilizing spray-drying technology. The purple corn (Zea mays L.) used in this study was from Peru; it was first processed by boiling the güiñapo at 100 °C 1 h, followed by cooling and fermenting under controlled conditions for 5–7 days until achieving the desired characteristics referenced from previous studies, such as pH, alcohol content (v/v), and degrees Brix. Upon attaining the desired fermentation characteristics, the ChG was centrifuged, filtered, and dehydrated by spray-drying technology with the following parameters: air inlet temperature (165 °C), airflow (0.89 mL/min), feed flow (1.67 mL/min), and outlet temperature (93 °C). These optimal parameters were determined using the response surface methodology after 15 runs. Then, a fine purple powder was produced with 6.61% moisture, pH 4.83, and 1.5 °Brix. The results of proximal analysis before and after spray-drying were for carbohydrates (1.77% to 82.67%), ash (0.02% to 4.91%), protein (0.10% to 5.81%), and alcohol (3.17% to 0.64%). This study highlights the biodiversity, sustainability, and food security of ancestral crops to contribute to cultural heritage valorization.